Plasma Docosahexaenoic Acid and Eicosapentaenoic Acid Concentrations Are Positively Associated with Brown Adipose Tissue Activity in Humans - Angie S. Xiang; Corey Giles; Rebecca K.C. Loh; Melissa F. Formosa; Nina Eikelis; Gavin W. Lambert; Peter J. Meikle; Bronwyn A. Kingwell; Andrew L. Carey (Metabolites, 2020)
Brown adipose tissue (BAT) activation is a possible therapeutic strategy to increase energy expenditure and improve metabolic homeostasis in obesity. Recent studies have revealed novel interactions between BAT and circulating lipid species—in particular, the non-esterified fatty acid (NEFA) and oxylipin lipid classes. This study aimed to identify individual lipid species that may be associated with cold-stimulated BAT activity in humans. A panel of 44 NEFA and 41 oxylipin species were measured using mass-spectrometry-based lipidomics in the plasma of fourteen healthy male participants before and after 90 min of mild cold exposure. Lipid measures were correlated with BAT activity measured via 18F-fluorodeoxyglucose ([18F]FDG) positron emission tomography/computed tomography (PET/CT), along with norepinephrine (NE) concentration (a surrogate marker of sympathetic activity). The study identified a significant increase in total NEFA concentration following cold exposure that was positively associated with NE concentration change. Individually, 33 NEFA and 11 oxylipin species increased significantly in response to cold exposure. The concentration of the omega-3 NEFA, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) at baseline was significantly associated with BAT activity, and the cold-induced change in 18 NEFA species was significantly associated with BAT activity. No significant associations were identified between BAT activity and oxylipins.